Metaverse-Based Activities for Enhancing Communicative Competencies among Young Learners - Tan, Kim Hua; Mohd Khair Naim; Wahiza Wahi; Ahmad Firdaus Arham; Yunos, Nasruddin (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The transformative potential of the metaverse in English language learning, particularly in rural areas such as the Felda (Federal Land Development) Malaysian communities, has gained popularity following the COVID-19 outbreak. This study explores the use of metaverse-based activities to enhance communicative competencies among young learners in these rural areas. Employing a quantitative methodology, the research involves 60 participants divided evenly into two groups: an experimental group and a control group. The former received metaverse-based English language instruction, while the latter followed traditional classroom teaching. Results from pre- and post-tests, as well as structured questionnaires, indicate that the metaverse significantly improves communication competencies, including speaking, listening, and social interaction skills. The data show that metaverse-based activities provide a more engaging and immersive learning environment, promoting natural and authentic improvements in communicative abilities for young children in rural primary schools. These findings hold significant implications for English language instructors and curriculum designers, highlighting the potential of integrating modern technology into early childhood education.